The effect of PBL teaching method in the teaching of congenital malformation - Li, Hua; Cai, Zejun; Liu, Yue; Chen, Yong; Lin, Qiaomei; Liu, Hui (Frontiers in Medicine, 2025)
ObjectiveTo explore the effect of PBL (Problem-Based Learning) teaching method in the teaching of congenital malformation.MethodsThe application of PBL teaching method in the teaching process of congenital malformations among clinical medicine majors in grades 2021 and 2022. And the effect of PBL teaching method in teaching congenital malformations was analyzed through pre-class intra-group evaluation, in-class inter-group evaluation, and post-class questionnaire survey.ResultsThere was a significant difference in inter-group evaluation scores during class, and a post-class questionnaire survey showed that students have made a qualitative leap in their understanding of congenital malformations after PBL teaching.ConclusionThe PBL teaching method enhances students’ teamwork ability, stimulates their innovative thinking, and enhances their interest in learning.